MIEJSCA PAMIĘCI NA TLE UNESCO 1972 WORLD HERITAGE CONVENTION ORAZ KRYTERIUM VI WYTYCZNYCH OPERACYJNYCH JEJ STOSOWANIA - Wojciech Kowalski (Ochrona Dziedzictwa Kulturowego, 2017)
Author argues that places of memory can be protected under 1972 UNESCO World Heritage Convention as definition of heritage (art. 1) encompasses „historical value” criterion in relation to all elements of this heritage, namely to monuments, groups of buildings and sites. Such thesis is strongly supported by practical application of criterion VI of Operational Guidelines by World Heritage Committee. Almost all monuments and sites inscribed on the World Heritage List under this criterion are to maintain memory of important events, beliefs, ideas etc. Intangible component was therefore a basis of these inscriptions although presence of material component as “a witness” was also important. It is however specially interesting to note that the Auschwitz Birkenau German Nazi Concentration Camp (1940-1945) was inscribed as the only one symbol of Holocaust what was underlined by the condition that no other such monuments would be inscribed in the future. It seems clear that by this fact the new principle of „symbolic representation” was adopted by Committee. The problem is that such principle has no legal basis, in particular it cannot be found in the 1972 Convention and for this reason decision establishing it is not binding for future inscriptions. Taking into account delicate and sometimes even political nature of inscription of some places of memory it seems reasonable that already existing practice of „serial inscriptions” can be adopted as a solution in cases of similar sites. It should make possible to leave apart the policy of „symbolic representation” as not only legally defective but leading also to situation where several places of memory of universal importance for whole humanity will stay without any legal protection.